Enzymes of an alternative pathway of glucose metabolism in obligate methanotrophs - Olga N. Rozova (Nature Portfolio, 2021)
Abstract Aerobic methanotrophic bacteria utilize methane as a growth substrate but are unable to grow on any sugars. In this study we have shown that two obligate methanotrophs, Methylotuvimicrobium alcaliphilum 20Z and Methylobacter luteus IMV-B-3098, possess functional glucose dehydrogenase (GDH) and gluconate kinase (GntK). The recombinant GDHs from both methanotrophs were homotetrameric and strongly specific for glucose preferring NAD+ over NADP+. GDH from Mtm. alcaliphilum was most active at pH 10 (V max = 95 U/mg protein) and demonstrated very high K m for glucose (91.8 ± 3.8 mM). GDH from Mb. luteus was most active at pH 8.5 (V max = 43 U/mg protein) and had lower K m for glucose (16 ± 0.6 mM). The cells of two Mtm. alcaliphilum double mutants with deletions either of the genes encoding GDH and glucokinase (gdh ─/glk ─) or of the genes encoding gluconate kinase and glucokinase (gntk ─/glk ─) had the lower glycogen level and the higher contents of intracellular glucose and trehalose compared to the wild type strain. The gntk ─/glk ─ knockout mutant additionally accumulated gluconic acid. These data, along with bioinformatics analysis, demonstrate that glycogen derived free glucose can enter the Entner–Doudoroff pathway or the pentose phosphate cycle in methanotrophs, bypassing glycolysis via the gluconate shunt.